THE ASSOCIATIVE EXPERIMENT IN LANGUAGE TEACHING - Gayubova Komila Anvarovna, (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The article describes the issues of studying the features of mnemic activity with the ultimate goal of forming mnemic skills. This can be interpreted as a similarity between the action of associative reproduction of words and the work of memory to actualize verbal material, which inevitably enters into any language learning.